Mathemathics for elementary teachers : - Bennett, Albert B. (McGraw-Hill, 2004)
This book is designed for courses in mathematics for instructors who choose to focus on and/or take an activities approach. This book provides inductive activities for prospective elementary school teachers and incorporates the use of physical models, manipulatives, and visual images to develop concepts and encourage higher level thinking. (This text contains activity sets, one corresponding to each section of the companion text, Mathematics for Elementary Teachers: A Conceptual Approach (also by Bennett/Nelson). The Activities Approach text can be used independently or along with its companion volume.)